The role of root dynamics on the climate sensitivity of ecohydrological processes of over- and understory in a semi-arid groundwater-dependent ecosystem - Liu, Qiyue; Barros, Ana P. (Frontiers in Environmental Science, 2024)
Plant roots connect belowground moisture with aboveground vegetation functionalities, making root plasticity critical for drought resilience. This study employs an enhanced land surface ecohydrological model, Duke Coupled Hydrology Model with Vegetation and Dynamic Roots (DCHM-VDR), to investigate how root dynamics affect vegetation adaptation under a range of climate conditions. DCHM-VDR features a moisture-driven root parameterization that simulates dynamic root profiles and hydraulic redistribution (HR). Applied to a semiarid woodland with groundwater-dependent mesquites and shallow-rooted shrubs, model results compare well against AmeriFlux tower data and capture observed soil moisture patterns tied to root water uptake, including mesquite’s dimorphic root profile and shifts in water source and the direction of HR. Accounting for HR lowers overall water use efficiency (WUE) by more than 50% in the dry season due to release of deep root water uptake to moisten dry soil layers. Dynamic root profiles reduce water demand by avoiding dry soil patches and utilizing moist layers with increased WUE, especially for shrubs. Mesquites with a dimorphic root profile show a 3-fold annual transpiration (Tr) increase from 183 mm to 629 mm/year and reduced HR/Tr from 34% to 6%, along with a small reduction of around 10% for shrubs, reflecting the importance of groundwater sourcing and the codependence of shrubs on mesquite for water stress resilience. Future climate scenarios were examined using the Thermodynamic Global Warming downscaled data. Mesquites and shrubs respond positively to wetter winters, albeit with opposite water use strategies in the drier growing seasons due to different rooting depths and HR modulation of soil moisture. Mesquites increase transpiration by adjusting root fraction, water uptake, and HR closer to the saturated zone, while shrubs reduce transpiration and increase WUE by 17% compared to a decrease of 13% in mesquite WUE under the driest scenario. The intertwined water use strategies of mesquites and shrubs expressed by the root water uptake dynamics determine ecosystem response aboveground under more extreme climate conditions, highlighting the importance of modeling root architecture dynamics and co-adaptive ecohydrological processes in predicting ecosystem responses to climate change.